A Panel Data Analysis of Capital Structure Determinants: An Empirical Study of Non-Financial Firms in Oman - Singh, Dharmendra (International Journal of Economics and Financial Issues, 2016)
The aim of this research paper is to examine the firm-specific determinants of the capital structure for non-financing companies of Oman. Based on the existing literature and theories of capital structure, the probable determinants of capital structure are identified. The analysis is performed using panel data techniques; fixed and random effects, for a sample of 61 companies listed on the Muscat Securities Market during 2011-2015.The results suggest that tangibility, profitability and liquidity are having negative relationship with the leverage, whereas firm size and growth opportunity are positively related to the leverage. Non-debt tax shields do not appear to be significantly related to leverage of Omani firms. Pecking order theory is most successful in explaining the determinants of capital structure of the Omani companies. The results of this paper suggest that findings are consistent with the capital structure studies on other developed and developing countries. The study has important policy implications for the finance managers of the firms in Oman. Keywords: Leverage, determinants, capital structure, Oman JEL Classification: G30